2007
DOI: 10.1002/kin.20266
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of reaction of copper with substituted benzyl chlorides in dipolar aprotic solvents

Abstract: The reaction of copper with benzyl chlorides in dipolar aprotic solvents has been investigated. The kinetic and thermodynamic parameters of the reaction of copper with benzyl chloride in dimethyl sulfoxide, dimethylacetamide, and hexamethylphosphoramide have been obtained. Hammett plots of log (k/k • ) versus the substituent constant σ gave good correlation. The structure of the organic group has little effect on the rate of reaction of benzyl chloride with copper. The kinetic and thermodynamic parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…The Hammett correlation classically is applied to predict the effects of substituents on reaction‐rate constants between organic compounds . Both inductive and resonance effects determine the kind of substituents.…”
Section: Resultsmentioning
confidence: 99%
“…The Hammett correlation classically is applied to predict the effects of substituents on reaction‐rate constants between organic compounds . Both inductive and resonance effects determine the kind of substituents.…”
Section: Resultsmentioning
confidence: 99%
“…Here, with [Me 6 ‐TREN] o = 0, no polymerization occurs, although activation followed by bimolecular termination takes place. Studies into the kinetics of Cu(0) mediated activation of benzyl halides and CCl 4 , indicated that even in the absence of an N‐ligand, carbon halide bond dissociation did occur with the fastest rate being observed in DMSO solvent 35–37. Without ligand, the extent and rate disproportionation of Cu(I)Br is significantly lower than in the presence of Me 6 ‐TREN.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in rate with increasing ligand concentration is consistent with Langmuir‐Hinshelwood kinetics previously proposed for Cu(0) activation of benzyl halides, if the solvent is replaced with more strongly coordinating N‐ligand (eqs 1– 3). 35–37 …”
Section: Resultsmentioning
confidence: 99%
“…The maximum wavelength of the absorption of the solution containing CuBr located at 281 nm originating from the absorption of Cu(II) complex, which further showed the disproportionation of Cu(I). Previous studies have indicated that SET‐LRP is mediated not only by the surface of Cu(0) but also by dissolved Cu(I)X species 37, 38. The proposed mechanism for SET‐LRP invokes the reversible activation of dormant halide chain‐ends via a Cu(0)‐mediated outer‐sphere electron transfer process involving the heterolytic CX cleavage 39–41.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that SET-LRP is mediated not only by the surface of Cu(0) but also by dissolved Cu(I)X species. 37,38 The proposed mechanism for SET-LRP invokes the reversible activation of dormant halide chain-ends via a Cu(0)-mediated outer-sphere electron transfer process involving the heterolytic CAX cleavage. [39][40][41] This mechanism also indicates that the disproportionation of CuBr in situ to generate Cu(0) activator and CuBr 2 deactivator is crucial for achieving kinetics, and the extent of disproportionation of CuBr is highly dependent on ligand and solvent chose.…”
Section: Synthesis Of Poly(nipam)smentioning
confidence: 99%